DARI SISTEM SPONSOR HINGGA BAWON: PROPAGANDA KOLONISASI DI JAWA, 1900-1941 - , AURA CUBANIMITA, Bahaâuddin, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Colonization was the Dutch East Indiesâ ethical politics implementation since the beginning of the 20th century. In spite of parsing the density of Java population, colonization also expected to boost the economic growth in the destination regions, which are the island outside Java. However, the migration process of Javanese is not an easy case because of socio-cultural and psychological factors. Therefore, the colonial government issued a series of propaganda in various media such as photographs, books, leaflets, and film that illustrate the potential for colonization region. The government also used Javanese cultural sym bols such as making use of the village chief as propagandist, organizing folk theaters, and using puppet figures in a number of media propaganda. This is expected to change the paradigm convince people of the tanah sabrang. In fact, these media were not entire successful to attract the Javanese people attention. For example, the screening of propaganda film, âTanah Sabrangâ was not able to raise the rate of departure colonist even though this was always flooded with thousands of people. Apparently Javanese people were more interested in the âwrapâ rather than its essence. The changing implementation of the colonization system from time to time also affects the amount of Javanese peopleâs interest in boyong. Colonization initially held with the freely system, those who depart are exempted from any cost, even given sufficient supplies. This system did not last long until the colonization experiences the absence of this system, in 1930